STRATEGIES TO IMPROVE BOND STABILITY AT THE INTERFACE BETWEEN DENTIN AND COMPOSITE RESIN - A REVIEW - Mihai-Octavian Boaru; Simona Stoleriu; Galina Pancu; Irina Nica; Mihaela Sălceanu; Ionut Tărăboanţă; Andra Claudia Tărăboanţă-Gamen; Gianina Iovan (Romanian Dental Association for Education, 2021)
The hybrid layer is the key for bonding between composite resins and mineralized dental tissues. Bonding to dentin is problematic because of the morphological complexity, high content of water and organic components, and lack of compatibility with hydrophobic monomers. Moreover, the stability of the hybrid layer is challenged over time by degradation phenomena that affects both components of the hybrid layer: the dentin organic matrix and the adhesive resin. Both degradation phenomena are the result of hydrolysis mechanisms involving the residual water preserved in the hybrid layer. The main problem continues to be the dentin collagen degradation determined by host-derived metal proteinases. Various strategies have been proposed to improve the bond stability at dentin-composite resin interface, which aim either to increase the resistance of demineralized dentin and resin to degradation or to decrease the residual water within the hybrid layer. Further studies should aim to identify the most effective combination adhesive - metalloproteinase inhibitor and the most suitable strategy for improved dentin hybridization and stability of the hybrid layer.